Perkawinan dalam Perspektif Hukum Adat Indonesia: Ragam Sistem, Tradisi, dan Tantangan Modern - Damayanti, Elvira; Nurlita, Divani 'Aina; Arya Putra, Daffa Arjuna (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Marriage in Indonesia’s customary communities is not merely a legal union between two individuals, but a socio-cultural institution imbued with symbolic meanings and noble values. Customary law, as a living legal system within society, comprehensively governs all aspects of marriage from the proposal process to the resolution of marriage dissolution. The academic concern that underpins this study lies in the limited understanding of the complexity of customary marriage systems amidst the tide of modernization and the dominance of formal legal norms, which often overlook local legal diversity. This paper employs a descriptive qualitative method with a normative-legal and sociological approach. The data are collected through literature studies exploring various sources on customary law and legal anthropology to identify and elaborate on the concepts, forms, and systems of customary marriage, engagement procedures, ceremonial stages, property arrangements, and the legal consequences of marital dissolution from a customary law perspective. The findings indicate that each customary community In Indonesia possesses distinctive characteristics in conducting marriages, reflecting their kinship systems, social structures, and deeply held cultural values. The customary marriage process serves not only as a family event but also as a vehicle for preserving collective identity and social norms. Therefore, customary law in the context of marriage remains socially relevant and holds significant potential to contribute to the development of a pluralistic and context-sensitive national legal system.